A technique for introducing looped sutures in flexor tendon repair - Jagannath, Kamath B; Praveen, Bhardwaj (Indian Journal of Plastic Surgery, 2006)
Stronger flexor tendon repairs facilitate early active motion therapy protocols. Core sutures using looped suture material provide 1 ½ to twice the strength of Kessler′s technique (with four strand and six strand Tsuge technique respectively). The technique is well-described and uses preformed looped sutures (supramid). This is not available in many countries and we describe a technique whereby looped sutures can be introduced in flexor tendon repair by the use of 23 G hypodermic needle and conventional 4.0 or 5.0 sutures. This is an alternative when the custom made preformed sutures are not available. This can be practiced in zone 3 to zone 5 repairs. Technical difficulties limit its use in zone 2 repairs.
Keywords: Flexor tendon repair; modified looped suture